Nonintegrating Lentiviral Vector-Based Vaccine Efficiently Induces Functional and Persistent CD8+ T Cell Responses in Mice. (19th May 2010) - Negri, Donatella R. M.; Michelini, Zuleika; Baroncelli, Silvia; Spada, Massimo; Vendetti, Silvia; Bona, Roberta; Leone, Pasqualina; Klotman, Mary E.; Cara, Andrea
Abstract : CD8+ T cells are an essential component of an effective host immune response to tumors and viral infections. Genetic immunization is particularly suitable for inducing CTL responses, because the encoded proteins enter the MHC class I processing pathway through either transgene expression or cross-presentation. In order to compare the efficiency and persistence of immune response induced by genetic vaccines, BALB/c mice were immunized either twice intramuscularly with DNA plasmid expressing a codon-optimized HIV-1 gp120 Envelope sequence together with murine GM-CSF sequence or with a single immunization using an integrase defective lentiviral vector (IDLV) expressing the same proteins. Results strongly indicated that the schedule based on IDLV vaccine was more efficient in inducing specific immune response, as evaluated three months after the last immunization by IFNγ ELISPOT in both splenocytes and bone marrow- (BM-) derived cells, chromium release assay in splenocytes, and antibody detection in sera. In addition, IDLV immunization induced high frequency of polyfunctional CD8+ T cells able to simultaneously produce IFNγ, TNFα, and IL2.